The Effect of Instagram Ads, Prices and Halal Labeling of KFC Fast Food Restaurants on Purchase Decisions: Pengaruh Iklan Instagram, Harga dan Labelisasi Halal Restoran Cepat Saji KFC terhadap Keputusan Pembelian - Shella Titania Nurdin; Fitri Nur Latifah (Academia Open, 2021)
This study aims to determine the effect of Instagram advertising variables, prices, and halal labeling KFC fast food restaurants on purchasing decisions of students at Muhammadiyah University of Sidoarjo using quantitative methods. The sample size was taken as many as 99 respondents with stratified random sampling method. The results of this study indicate that there is a simultaneous influence between Instagram Advertising, Price and Halal Labeling variables on purchasing decisions with a fcount value of 26.933 > ftable 2.70 and a sig value of 0.000 <0.05. While the partial results of the Instagram Ads variable have a tcount value of 3,391 > ttable 1,988, the Price Variable has a tcount value of 4.708 > 1,988 and the Halal Labeling Variable has a tcount value of 2,978 > 1,988. So it can be concluded that the three variables in this study have a positive and significant influence on purchasing decisions for students at the Muhammadiyah University of Sidoarjo